Community Diagnosis: an Overview of the Incidence of Pediculosis Capitis Infection at Dharma Laksana Orphanage - Ida Ayu Made Mahayani; Nadira Yumna (Indonesian Journal of Global Health Research, 2023)
Pediculosis capitis or head lice are ectoparasites that live on the human scalp. Children are more often affected by Pediculosis capitis. One of the factors causing Pediculosis capitis is poor personal hygiene. The purpose of this study was to analyze descriptively the incidence of Pediculosis capitis infection at Dharma Laksana Orphanage with a community diagnosis approach. This was a cross-sectional study with a sample of 40 orphanages. The variables of this study were level of knowledge, education, personal hygiene, occupancy density, gender, age, and Pediculosis capitis incidence. Questionnaires were distributed to the Dharma Laksana Orphanage community at one time with the questionnaire explained first. Data was collected and processed using SPSS and analyzed univariately (descriptively). A total of 62.5% of the orphanage community experienced the incidence of Pediculosis capitis. Most members of the orphanage community have poor knowledge (67.5%) and poor personal hygiene (57.5%) regarding the prevention of Pediculosis capitis. Intervention in the form of counseling through posters and videos about Pediculosis capitis and the administration of 1% permethrin (peditox) to reduce the spread of Pediculosis capitis are needed.